Roles and challenges of Islamic micro finance institutions in Malaysia - Md Nor, Mohd Zakhiri (2014)
The Islamic micro finance industry begins to develop rapidly in Malaysia.A number of institutions have demonstrated that they contribute to the socio-economic development of the nation. Nevertheless, a number of issues arose as to the governance of Islamic micro finance in Malaysia. Accordingly, this study examines the roles and challenges of Islamic micro finance institutions in Malaysia. The objectives are three-fold, i.e. (1) to examine the roles contributed by the micro financing activities in Malaysia, (2) to explore issues and challenges faced by micro financing in Malaysia, and (3) to analyse the viability of developing a commercially-driven regulatory framework for Islamic micro financing institutions in Malaysia. Adopting a qualitative method, the researcher engaged in both library based research (to review literature s and current legal frameworks) as well as field work (case study on four units of analysis involving stakeholders of information). In total, ten respondents were interviewed using the semi-structured interviews instrument. The research found that there exist numerous issues and challenges facing the micro financing activities in Malaysia, there is moderate level of knowledge and awareness of the regulatory requirements of micro financing in Malaysia on part of the stakeholders of information, and also it is viable to develop a commercially-driven regulatory framework for Islamic micro financing institutions in Malaysia.This study is significant in determining the viability of introducing such framework within the ambit of the current legal framework governing Islamic banking and finance industry in Malaysia.